2012
DOI: 10.2174/157340612799278595
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Pain Relief by Low-Power Infrared Irradiation: ATP is an IR-Target Molecule in Nociceptive Neurons

Abstract: Effects of infrared (IR) radiation generated by a low-power CO2-laser on the membrane of cultured dissociated nociceptive neurons of newborn rat spinal ganglia were investigated using the whole-cell patch-clamp method. Low-power IR radiation diminished the voltage sensitivity of activation gating machinery of slow sodium channels (Na(v)1.8). Ouabain known to block both transducer and pumping functions of Na+,K+-ATPase eliminated IR irradiation effects. The molecular mechanism of interaction of CO2-laser radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…In an in vitro study, Yachnev et al . found a reduction in the activation of sodium channels dependent on neurons of the dorsal ganglia of Wister rats irradiated with infrared LLLT (fluencia: 10 −11 J cm −2 ) decreasing the action potential on sensitive neurons.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In an in vitro study, Yachnev et al . found a reduction in the activation of sodium channels dependent on neurons of the dorsal ganglia of Wister rats irradiated with infrared LLLT (fluencia: 10 −11 J cm −2 ) decreasing the action potential on sensitive neurons.…”
Section: Discussionmentioning
confidence: 93%
“…These findings demonstrate improvements, but irradiation was only performed over the injured nerve and the injury model was that of chronic constriction, demonstrating that LLLT has the effect of diminishing the stimulation of nociceptive receptors. In an in vitro study, Yachnev et al (27) found a reduction in the activation of sodium channels dependent on neurons of the dorsal ganglia of Wister rats irradiated with infrared LLLT (fluencia: 10 À11 J cm À2 ) decreasing the action potential on sensitive neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Absorption of red or infrared (IR) photons by cytochrome c oxidase in the mitochondrial respiratory chain causes an increase in cellular respiration with increasing of ATP synthesis . Further cellular effects induced by LLL also include changes in intracellular calcium , modulation of activity of Na + K + ATPase , photodissociation of nitric oxide , and increasing concentration of cyclic adenosine monophosate . All these changes can affect a number of important cellular processes which are supposed to be related to the therapeutic effects of LLL application in various medical conditions .…”
Section: Introductionmentioning
confidence: 99%
“…A further report indicated that the reason why pain was relieved by low‐power infrared irradiation was that it probably induced Na + , K + ‐ATPase signal‐transducing and pumping functions . On the contrary, low‐power infrared irradiation to the nociceptive neuron was suggested to diminish the voltage sensitivity of activation gating machinery of slow sodium channels . Further investigation is required to clarify the functional mechanism of SGR for working on ANS and the relationship between the healing process of BMS and autonomic instability.…”
Section: Discussionmentioning
confidence: 99%